Medical Cannabis Activity Against Inflammation: Active Compounds and Modes of Action - Anil, Seegehalli M.; Peeri, Hadar; Koltai, Hinanit (Frontiers in Pharmacology, 2022)
Inflammation often develops from acute, chronic, or auto-inflammatory disorders that can lead to compromised organ function. Cannabis (Cannabis sativa) has been used to treat inflammation for millennia, but its use in modern medicine is hampered by a lack of scientific knowledge. Previous studies report that cannabis extracts and inflorescence inhibit inflammatory responses in vitro and in pre-clinical and clinical trials. The endocannabinoid system (ECS) is a modulator of immune system activity, and dysregulation of this system is involved in various chronic inflammations. This system includes cannabinoid receptor types 1 and 2 (CB1 and CB2), arachidonic acid-derived endocannabinoids, and enzymes involved in endocannabinoid metabolism. Cannabis produces a large number of phytocannabinoids and numerous other biomolecules such as terpenes and flavonoids. In multiple experimental models, both in vitro and in vivo, several phytocannabinoids, including Δ9-tetrahydrocannabinol (THC), cannabidiol (CBD) and cannabigerol (CBG), exhibit activity against inflammation. These phytocannabinoids may bind to ECS and/or other receptors and ameliorate various inflammatory-related diseases by activating several signaling pathways. Synergy between phytocannabinoids, as well as between phytocannabinoids and terpenes, has been demonstrated. Cannabis activity can be improved by selecting the most active plant ingredients (API) while eliminating parts of the whole extract. Moreover, in the future cannabis components might be combined with pharmaceutical drugs to reduce inflammation.